Knowledge, attitude, and practices of Saudi Dental students regarding oral/oropharyngeal cancer: A cross-sectional study - Bader Fatani; Abdulaziz Abdullah Alabood; Raghad Fahad Almuqrin (Wolters Kluwer Medknow Publications, 2022)
Background: Oral cancers are well known for their disastrous and fatal consequences. This type of cancer manifests itself in various forms, ranging from simple ulcerative lesions to proliferative growths. The reduction of morbidity and mortality of cancer can be achieved via its early recognition through screening and patient awareness and can improve the outcome of the disease comparatively. Even though most of the dentists who were surveyed said that they are inclined to provide head-and-neck examinations for their patients, studies show that dentists generally lack the knowledge required for diagnosing oral cancer lesions. Objective: This study aims to assess and evaluate the knowledge, attitude, and practices of dental students regarding oral cancer at King Saud University. Materials and Methods: The data were collected from the dental students at King Saud University in Riyadh, Saudi Arabia, from May 2021 to August 2021. The targeted subjects were dental students - male and female students older than 20 years - studying at King Saud University. Results: A sample of 206 dental students was analyzed. It was found that most dental students have heard about oral cancer (93.2%) and knew that it was preventable (77.7%). They also knew that it was treatable (93.7%) and has the ability to metastasize (93.2%). The relationship between the knowledge of oral cancer and the gender of the students was not statistically significant (all P > 0.050). There were significant relationships between oral cancer knowledge and age of the student (P < 0.001) and oral cancer treatability and age (P = 0.002). Similarly, oral cancer knowledge (P ≤ 0.001), treatability knowledge (P = 0.007), and metastasis knowledge (P = 0.030) were significantly related to the progression of academic years. Conclusion: Our study showed that dental students have significant knowledge and awareness regarding oral cancer including the clinical appearance, signs, and symptoms of oral cancer. Moreover, few dental students even considered themselves very well informed and qualified to detect oral cancer in patients. Therefore, we assume that increasing the dental students' clinical practice as well as their self-confidence could highly influence the early detection of oral cancer for patients in future.